Sight‐threatening Graves' orbitopathy: Twenty years' experience of a multidisciplinary thyroid‐eye outpatient clinic. (19th November 2018) - Tramunt, Blandine; Imbert, Philippe; Grunenwald, Solange; Boutault, Franck; Caron, Philippe
Summary: Context: Sight‐threatening Graves' orbitopathy affects 3% to 5% of patients with Graves' orbitopathy. Objectives: To describe the management of patients with sight‐threatening Graves' orbitopathy seen in a multidisciplinary thyroid‐eye outpatient clinic dedicated to Graves' orbitopathy (GO). Patients and methods: We enrolled all patients with sight‐threatening GO (dysthyroid optic neuropathy and corneal ulcer as defined in the EUGOGO statement) seen and treated in our GO multidisciplinary thyroid‐eye outpatient clinic over the last two decades. Results: A total of 31 patients (median age 51 years old) including 24 women (77%) and 58% active smokers. This population represented 47 cases (case = eye) of sight‐threatening GO. Dysthyroid optic neuropathy (DON) occurred in 40 eyes, corneal ulcer in 15 eyes and both in 8. At presentation, the clinical features of DON were reduced visual acuity (85%), visual field defects (80%), optic disc swelling (42%) and reduced colour vision (100%). At one year, surgical orbital decompression (OD) was performed in 82.5% of DON cases. Only seven eyes with DON were treated with pulses of intra‐venous glucocorticoids. For 10 patients, several therapeutic strategies (OD n = 4, punctal plug n = 1, amniotic membrane graft n = 2, tarsorrhaphy n = 2, botulinum toxin injection = 3 and eyelid surgery n = 2) were used to treat corneal ulcer. For each ophthalmological parameter, more than 85% of DON cases had recovery or improvement after treatment. For visual acuity in corneal ulcer, it was 71.4%. Conclusion: We report 47 cases of sight‐threatening GO. Orbital decompression was performed in the majority of DON cases and several therapeutic strategies were necessary to treat corneal ulcer. The results are satisfactory in sight‐threatening Graves' orbitopathy due to multidisciplinary management.